Peningkatan Kemampuan Membaca Pemahaman Pada Mata Pelajaran Bahasa Indonesia Melalui Media Buku Cerita Bergambar Siswa Kelas II SDN 003 Loa Janan Ilir - Farida Maulida; Nanda Shaqinah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to describe the implementation of picture book media and to determine the improvement in reading comprehension skills of second-grade students at SDN 003 Loa Janan Ilir through the use of picture books in Indonesian language learning. This research employs a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, implemented in two cycles. The research subjects consisted of 25 second-grade students at SDN 003 Loa Janan Ilir for the 2024/2025 academic year. Data collection techniques included reading comprehension tests, classroom observation of teacher and student activities, and semi-structured interviews with the class teacher. Results demonstrated significant improvement in students' reading comprehension. In the pre-cycle phase, the class average was only 54.6 with a classical mastery rate of 20.0%. After Cycle I, which employed a read-aloud strategy using the story "The Ant and the Grasshopper," the average increased to 66.6 with a mastery rate of 44.0%. In Cycle II, which applied picture walk and think-pair-share strategies using the story "The Arrogant Rabbit and the Persistent Turtle," the class average reached 79.1 with a classical mastery rate of 92.0% (23 out of 25 students). Teacher activity reached 98% and student activity reached 90%, both in the "Very Good" category. This study concludes that the use of picture book media integrated with appropriate learning strategies is proven effective in improving reading comprehension skills of second-grade elementary school students.